Identification of Escherichia coli Multidrug Resistance in Cattle in Abattoirs - Mustika, Yolla Rona; Effendi, Mustofa Helmi; Puspitasari, Yulianna; Plumeriastuti, Hani; Khairullah, Aswin Rafif; Kinasih, Kurnia Nisa (Universitas Airlangga, 2024)
Escherichia coli is a typical flora of an animals' digestive tract. Based on these details, this study was done on the detection and identification of multidrug-resistant E. coli in cattle in Surabaya abattoirs. Each cattle rectum swab sample was streaked into EMB agar media and followed by Gram staining. The IMViC test was used to confirm the presence of E. coli. Based on morphological culture features, Gram staining, and biochemical testing, the sample examination results revealed that 41 samples (41%) of the 100 cattle rectal swab samples that were isolated were confirmed to be positive for E. coli. The profile of antibiotic resistance from the results of the E. coli resistance test to antibiotics showed that out of a total of 41 isolates of E. coli, 12 isolates (29.27%) were detected as resistant to 1 class of antibiotics tested, while 2 isolates (4.88%) were resistant to 2 classes of antibiotics, and 3 isolates (7.32%) were confirmed to be multidrug resistance (MDR).